Liberalizing higher education system in Malaysia through the implementation of creativity and innovation in its subjects - Thiruchelvam, Cheryl Chelliah; Abdullah, Sarena (Department of Southeast Asian Studies, University of Malaya Kuala Lumpur, Malaysia, 2013)
In the last decade, Malaysia launched k-economy (knowledge economy) as a step forward to move from its production based economy towards enriching its human capital. A move to face escalating challenges due to globalization; to mature from a „developing nation‟ into a „developed nation‟. Even though many creative and innovative programmes were implemented in the entertainment and education industry, as well as in government and private sectors; the local graduates and work force were still unprepared to face the ultimate forces of globalization as it reached our shores. Other developed nations; the United States, Australia and New Zealand are in the midst of revolutionizing their education system; not only at the tertiary level, but even at the pre-school level. As such, the Malaysian Higher Education System should not only be producing stereotyped graduates in quantities, but should take this opportunity to revolutionize, diversify and develop its education system to produce quality graduates for the betterment and advancement of its society. Therefore this paper intends to discuss the importance of the k-economy and the reality of the current Local Higher Education and put forth a few suggestions to liberalize the higher education system in Malaysia.